Qualitative Study: Culture of Post-Partnership Care in The Outer Baduy Tribe in Kanekes Village, Leuwidamar District, Lebak Regency, Banten Province - Ernawati; Shinta Novelia; Rukmaini (International Journal of Midwifery and Health Sciences, 2025)
Background: Maternal and child health problems are inseparable from socio-cultural and environmental factors in the community where they live. Whether we realize it or not, traditional beliefs and knowledge factors, such as concepts regarding various taboos, causal relationships, concepts about healthy and sick, and habits, sometimes have a positive or negative impact on maternal and child health (MCH). Objective: The aim is to analyze health behavior during the postpartum period, both those that conflict with or do not conflict with health in the Outer Baduy Tribe in Kanekes Village, Leuwidamar District, Lebak Regency, Banten Province. Methodology: This study uses a qualitative phenomenological method through a triangulation approach. It took data from 10 informants (6 key informants and 4 supporting informants), and saturation was achieved when no new information was obtained on the same question. Data collection could be stopped, and the number of informants was not increased. Data analysis in this study used the Colaizzi nine-step technique. Results: The results of the study showed that the culture of postpartum care in the Outer Baduy tribe is contrary to health, namely not being allowed to take a nap, the culture of nyanda for 7 days, the prohibition of consuming eggs and sea fish during the postpartum period, the use of octopus for 1-3 months and cleaning the vagina from back to front. Treatments that do not conflict are the mobilization process, urination and defecation, the breastfeeding process, and breast care. Conclusions: Postpartum care in the Outer Baduy tribe still includes treatments that are contrary to health, but some treatments are by evidence-based obstetrics. It is recommended for health service officers to make it easier to determine a more appropriate approach strategy to change community health behavior towards healthy behavior.